School Strategy in Overcoming Students' Bullying Behavior at SMP Negeri 44 ST. Petrus Kloangpopot Kloangpopo Village, Doreng District, Sikka District - Dabura, Maria Ekarini; Kepalet, Petrus (Lembaga Riset Mutiara Akbar, 2023)
The results of the study stated that SMP Negeri 44 St. Petrus Kloangpopot has experienced bullying behavior. The type of bullying behavior that often occurs is verbal bullying and one of the factors that influences bullying behavior at St. Petrus Kloangpopot is the peer factor. As a result of this bullying behavior, there are children who feel insecure and feel inferior so that these children decide to drop out of school or change schools. From this problem, one of the schools that can prevent this bullying behavior is the principal, student council, homeroom teacher and Pancasila and Citizenship Education Teacher (PPKN) at SMP Negeri 44 St. Petrus Kloangpopot. From the results of the study, the authors conclude that bullying is a negative action or behavior that causes someone to be uncomfortable/injured